COVID-19 vaccine hesitancy among adults in Hawassa City Administration, Sidama Region, Ethiopia: A community-based study - Yohannes, Seblewongel; Alemayehu, Akalewold; Woldesenbet, Yohannes Markos; Tadele, Temesgen; Dangiso, Desta; Birhanu, Muntasha; Woldesemayat, Endrias Markos (Frontiers in Public Health, 2023)
Objective The COVID-19 vaccine is one of the key measures to control the disease. However, some people are hesitant to take the vaccine. The objective of this study was to assess COVID-19 vaccine hesitancy and associated factors among adults in Hawassa City Administration, South Ethiopia. Method From March 1 to 30, 2022, we conducted a community-based cross-sectional study among randomly selected 622 adults in Hawassa City Administration. A multi-stage sampling technique was used to recruit the study participants. Data were collected through a pretested structured questionnaire that was administered by four trained high school graduates. Data entry and analysis were done using the SPSS version 20 statistical package. Descriptive statistics and logistic regression analysis were performed. Statistically significant associations were reported at p-value <0.05. Result Among the participants, 400 of them (64.3%) had a high level of knowledge about the COVID-19 vaccine) and 425 of them (68.3%) had a positive attitude toward the COVID-19 vaccine. The level of vaccine hesitancy was 165 (26.5%) and vaccine acceptance was 457 (73.5%). The main reason for willingness to take the vaccine was to protect oneself from COVID-19 (364 participants, 58.5%), and for unwillingness, it was fear of the vaccine (154 participants, 24.8%). Mass media was the main source of information about the vaccine (472 participants, 75.9%). Age (adjusted odds ratio (AOR): 2.1, 95% CI: 1.2–3.7), religion (AOR: 2.6, 95% CI: 1.1–5.9), history of COVID-19 disease (AOR: 4.6, 95% CI: 1.4–14.9), knowledge related to the COVID-19 vaccine (AOR: 1.9, 95% CI: 1.2–3.1), and attitude toward the COVID-19 vaccine (AOR: 13.2, 95% CI: 8.3–20.9) were factors associated with vaccine hesitancy. Conclusion A low proportion of COVID-19 vaccine hesitancy was observed among our study participants. Improving people's awareness could help to improve vaccine acceptance. It is important to focus interventions on the identified risk factors of vaccine hesitancy.